The effectiveness of price limit: evidence from the Shanghai Stock Exchange - Lin, Jing (2007)
It has been much discussion among government regulators, academics and investors to control the increasing volatility by adopting the price limit mechanism in financial markets. Price limit are actively employed by stock markets as well as futures market worldwide. In conventional wisdom, price limit is perceived as a stock market regulatory mechanism which aim at preventing stock market from excessive fluctuations and therefore reduce volatility. This paper is to investigate whether price limit would moderate stock market volatility without affecting market liquidity and attempt to reveal the characteristics of those stocks that hit their price limit more frequently. We find that results from the SSE are consistent with conventional wisdom that stock market volatility is reduced as a result of the use of price limit. Secondly, trading volume increased significantly when stocks hit the daily price limit, and such behaviour will continue in the subsequent days. Finally, we find that stocks with large market capitalization hit their price limit more frequently.